How prepared is the retirement and residential aged care sector in Western Australia for older non-hetersexual people? - Horner, Barbara; McManus, Alexandra; Comfort, Jude; Freijah, Rita; Lovelock, G.; Hunter, M.; Tavener, M. (Radcliffe Medical Press Ltd., 2012)
Objective: To explore attitudes, knowledge and current practices of retirement and residential aged care providers in Western Australia towards accommodating older gay, lesbian, bisexual, transgender and intersex (GLBTI) individuals. GLBTI is used throughout as a general term to include people who are not exclusively heterosexual in identity, attraction and/or behaviour. Methods: Postal surveys were sent to 329 providers of accommodation to ask about their attitudes, knowledge and current practices towards older GLBTI people. Two focus groups were also held with managers of accommodation facilities and GLBTI community members. Results: Few respondents reported having experience with any older GLBTI residents in their retirement or residential aged care facility. There was poor inclusion of GLBTI issues in policy frameworks, and limited understanding regarding same-sex law reforms. Conclusion: Older non-heterosexual people are often obscured within ageing population discourses, and conceal their identity for fear of discrimination. GLBTI-sensitive practices can help to facilitate the disclosure of sexual orientation and/or gender identity that may assist in meeting the unique needs of this group.